Penerapan model pembelajaran E-Learning dan media sosial Pasca Covid-19 - khairunnisa nisa; Rana Upan H; Ainun Arbi H; Ade Iman S; Intan (Asosiasi Dosen Pemerhati Pendidikan Indonesia, 2022)
The purpose of this study was to determine the application of e-learning and social media learning models in social studies learning in junior high schools after the covid-19 pandemic. This research is analyzed by analysis of literature review. literature review is used to find out the strategies and steps taken by educators in designing e-learning- post-covid-19The results of research that have been carried out state that technology can help bring students to be competent, especially junior high school students who can work together to solve challenges in an education.Keywords: E-learning, Sosial Media, Covid-19 Keywords : E-Learning Pembelajaran IPS Sosial Media Covid-19